Multicentre, randomised, open-label, phase IV–III study to evaluate the efficacy of cloxacillin plus fosfomycin versus cloxacillin alone in adult patients with methicillin-susceptible Staphylococcus aureus bacteraemia: study protocol for the SAFO trial - Grillo, Sara; Cuervo, Guillermo; Carratala, Jordi; San-Juan, Rafael; Aguado, Jose M; Morata, Laura; Gomez-Zorrilla, Silvia; López-Contreras, Joaquín; Gasch, Oriol; Gomila-Grange, Aina; Iftimie, Simona; Garcia-Pardo, Graciano; et al. (BMJ open, 2021)
IntroductionMethicillin-susceptible Staphylococcus aureus (MSSA) bacteraemia is a frequent condition, with high mortality rates. There is a growing interest in identifying new therapeutic regimens able to reduce therapeutic failure and mortality observed with the standard of care of beta-lactam monotherapy. In vitro and small-scale studies have found synergy between cloxacillin and fosfomycin against S. aureus. Our aim is to test the hypothesis that cloxacillin plus fosfomycin achieves higher treatment success than cloxacillin alone in patients with MSSA bacteraemia.MethodsWe will perform a superiority, randomised, open-label, phase IV–III, two-armed parallel group (1:1) clinical trial at 20 Spanish tertiary hospitals. Adults (≥18 years) with isolation of MSSA from at least one blood culture ≤72 hours before inclusion with evidence of infection, will be randomly allocated to receive either cloxacillin 2 g/4-hour intravenous plus fosfomycin 3 g/6-hour intravenous or cloxacillin 2 g/4-hour intravenous alone for 7 days. After the first week, sequential treatment and total duration of antibiotic therapy will be determined according to clinical criteria by the attending physician.Primary endpoints: (1) Treatment success at day 7, a composite endpoint comprising all the following criteria: patient alive, stable or with improved quick-Sequential Organ Failure Assessment score, afebrile and with negative blood cultures for MSSA at day 7. (2) Treatment success at test of cure (TOC) visit: patient alive and no isolation of MSSA in blood culture or at another sterile site from day 8 until TOC (12 weeks after randomisation).We assume a rate of treatment success of 74% in the cloxacillin group. Accepting alpha risk of 0.05 and beta risk of 0.2 in a two-sided test, 183 subjects will be required in each of the control and experimental groups to obtain statistically significant difference of 12% (considered clinically significant).Ethics and disseminationEthical approval has been obtained from the Ethics Committee of Bellvitge University Hospital (AC069/18) and from the Spanish Medicines and Healthcare Product Regulatory Agency (AEMPS, AC069/18), and is valid for all participating centres under existing Spanish legislation. The results will be presented at international meetings and will be made available to patients and funders.Trial registration numberThe protocol has been approved by AEMPS with the Trial Registration Number EudraCT 2018-001207-37. ClinicalTrials.gov Identifier: NCT03959345; Pre-results.